Odpowiedzi

Najlepsza Odpowiedź!
2010-04-02T14:50:43+02:00
A) 5x² - 15x=5x(x-3)
b) 3by - 6b= 3b(y-2)
c) -8xy+8x=8x(-y+1)
d) 10a² - 2ab= 2a(5a-b)
e) xy -x²y= xy(1-x)
f) 6a - 24b + 30c= 6(a-4b+5c)
g)12ab² + 16b²=4b²(3a+4)
h) x³ - 2x² + x= x(x²-2x+1)
i) 2xy + 3x - x²y= x(2y+3-xy)
2010-04-02T14:51:49+02:00
A) 5x² - 15x=5x(x-3)
b) 3by - 6b=3b(y-2)
c) -8xy + 8x=-8x(y-1)
d) 10a² - 2ab=2a(5a-b)
e) xy - x²y=xy(1-x)
f) 6a - 24b + 30c=6(a-4b+5c)
g) 12ab²+ 16b²=4b²(3a+4)
h) x³ - 2x²+ x=x(x²-2x+1)=x(x-1)²
i) 2xy + 3x - x²y=x(2y+3-xy)=x[y(2-x)+3]
2010-04-02T14:54:49+02:00
A) 5x(x-3)
b) 3b(y-2)
c) 8x(-y+1)
d) 2a(5a - b)
e) xy(1-x)
f) 6(a - 4b +5c)
g) 4b²(3a+4)
h) x(x²-2x+1)
i) x(2y+3-xy)